Effect of Deposition Time on the Optoelectronics Properties of PbS Thin Films Obtained by Microwave-Assisted Chemical Bath Deposition. (3rd March 2019) - Barrios-Salgado, Enue; Rodríguez-Lazcano, Y.; Pérez-Orozco, Juan Pablo; Colin, J.; Altuzar, P.; Campos, J.; Quesada, David
Abstract : PbS thin films with thickness between 100 and 150 nm were grown for the first time by microwave-assisted chemical bath deposition in a commercial automated system with deposition times not exceeding 5 min. X-ray diffraction analysis shows that the thin films have cubic rock salt type structure with good crystallinity. The grain size increased from 18 to 20 nm, as the deposition time increased. Energy dispersive X-ray results confirm that the films are stoichiometric. Optical measurements show that thin films have relatively high absorption coefficients between 10 4 and 10 5 cm-1 in the visible range. In addition, the films exhibit a direct gap, within the energy range from 1.0 to 1.35 eV. The electrical properties, such as conductivity, the Seebeck coefficient, carrier concentration, and carrier mobility, are discussed.